Study of particle deposition in the Nano Aerosol Chamber In-Vitro Toxicity (NACIVT) System for determination of deposited doses onto cell cultures - Imtiaz,Rashed (2025)
Inhalation of engineered nanoparticles that are handled as powders or sprays in consumer products poses a potential health risk. To investigate the effects of nanoparticles on human health, the Nano Aerosol Chamber for In-Vitro Toxicity (NACIVT) system has been designed for controlled deposition of aerosol particles onto cell cultures. The objective of this study was to estimate the deposited dose onto the exposure areas and to investigate if the deposition varies between the different exposure wells using particles generated from both a solution of fluorescein salt and ZnO nanoparticles. Aerosolized particles were generated through an atomizer and deposited into the NACIVT chamber. The particle size distributions were measured with an SMPS and APS. Four experiments were conducted with fluorescein sodium salt of 10 µg/ml, and two different suspension of ZnO NPs were included. A spectrophotometer was employed to quantify the experimental deposited dose of fluorescein salt particles, whereas ICP-MS was utilized to obtain the experimental deposited dose of ZnO NPs. Both concentrations were compared to theoretically obtained doses using the size distributions from the SMPS and APS. Among the experiments with fluorescein salt, the deposited amount was estimated to be between 0.005 µg/ml and 0.011 µg/ml. In contrast, the doses obtained from the number concentration data were higher than the experimental values, ranging from 0.082 µg/ml to 0.140 µg/ml. One of the experiments showed higher, mass concentration, calculated number dose, and the surface area dose compared to other experiments. A similar pattern was observed in those doses when generating particles from the diluted suspension of ZnO NPs. The experimental deposition resulted in almost the same level on average (0.026 µg/ml) from the two suspensions of ZnO after collecting the particles from the NACIVT chamber. In contrast, the theoretically obtained doses accounted for around 6 µg/ml and 11.5 µg/ml with the atomizers’ suspensions of ZnO containing 88 µg/ml and 58 µg/ml, respectively. A little fluctuation was observed within the wells from the deposited salt particle in all the experiments; however, quite inconsistent mass concentrations were obtained from the wells exposed to ZnO NPs. The outcomes of the study demonstrate further optimization to minimize the variation between the experimental and theoretical doses as well as the variation within the wells.